Sprawling and Urban transportation system: Impacts in the city of Londrina, Parana, Brazil - Polidoro, M.; Lollo, J. A. de [UNESP]; Barros, M. V. F. (International Information and Engineering Technology Association, 2012)
After nearly 80 years since the construction of its core, represented today by the city's central area, Londrina, located in the state of Parana, has the appearance of a new city but its features and trends of planning policies depict the bad examples of Brazilian cities. With a booming urban growth, from north to south of the county, the urban interstices represented by big voids in the middle of the city created speculation and the concept of an ideal city slowly disappeared. With a metropolitan appearance and, at the same time, with small town aspects, Londrina stands out as an automobile-oriented city, a fact that has impacted the livelihood of the population, generating environmental impacts for all social classes. This paper discusses how the form of occupation in Londrina, characterized by the sprawl phenomenon and its relation to car preference as a mode of transportation has generated urban environmental impacts. It was concluded that the choice of using cars in Londrina, as well in other medium-sized Brazilian cities studied by the comparative method, has increased and has generated bottlenecks in traffic. As a consequence, there is a constant expropriation of properties for widening roads and at the same time, the presence of various densities and urban voids that form an uneven urban space and an obstacle to efficient urban planning. © 2012 WIT Press.
Keywords: Automobiles; Urban expansion; Urban growth; Urban sprawl; Urban transport; Comparative methods; Planning policies; Urban spaces; Urban transportation systems; Various densities; Environmental impact; Urban transportation; automobile; comparative study; environmental impact; urban planning; urban policy; urban transport; Brazil; Londrina; Parana [Brazil]